Genome sequencing of the Southern Ground Hornbill (Bucorvus leadbeateri) - Patel, Jasmin Bharatkumar (University of the Witwatersrand, Johannesburg, 2024)
The Southern Ground Hornbill (SGH – Bucorvus leadbeateri) is one of the largest hornbill species worldwide, known for its complex social structures and breeding behaviours. These birds, endemic to Africa, have been of great concern due to their declining populations and disappearance from historic ranges. Despite being the focus of numerous conservation efforts, with research forming an integral part of these initiatives, there is a lack of knowledge regarding the molecular biology aspects of this bird species. This study bridges the gap by presenting the first whole genome sequence of the SGH. The SGH genome was further explored using comparative genomics, genetic variant, and selection analysis, providing deeper insights into the evolution and adaptation of this species. Chapter 1 comprehensively reviews pertinent literature on various aspects of avian evolution, including the role genomics has played in elucidating how these species have adapted and evolved. Furthermore, the current body of knowledge on the SGH is explored. In Chapter 2 the entire genome sequence of the SGH was sequenced using Illumina short-read and Pacific BioSciences long-read datasets. Subsequently, the performance of various assembly approaches was evaluated to attain a high-quality assembly of the SGH. This was coupled with parameter optimisation and reference-based refinement to improve the SGH draft genome assembly. The final draft genome assembly was structurally annotated, providing insight into the genetic blueprint underpinning the SGH. Chapter 3 presents the comparative genomic analysis of the SGH with the genomes of available hornbill species from the genera Bucorvus (Bucorvus abyssinicus and SGH) and Buceros (Buceros bicornis and Buceros rhinoceros subsp. silvestris). This included analysis of the pangenome of the hornbill species, functional characterisation of the core and genus-specific elements of the pan-genome and analysis of orthogroups with evidence of paralogy. In Chapter 4, a species-level comparative genomic analysis of the SGH and the Abyssinian Ground Hornbill (AGH) was performed. Here differences in the species-specific proteome of the two species were analysed and the functional implications of these differences on the adaptation and survival of these species were evaluated. Furthermore, genetic variations between the SGH and AGH were identified and selection analysis of key protein-coding genes with high-impact variants was undertaken. This provided insight into the genetic diversity between the SGH and AGH. Finally, the implications of the study on the understanding of the genetic basis underlying the evolution and adaptation of the SGH is discussed and the future perspective of large-scale population genetic studies is provided.
A thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy, to the Faculty of Science, School of in Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Southern Ground Hornbill; Genome sequencing; De novo assembly; Annotations; Comparative genomics; Genetic variations; Selection analysis and conservation; UCTD; SDG-15: Life on land; SDG-17: Partnerships for the goals